The Regulation Of The Use Of Euthanasia In Indonesia And New Zealand In The Framework Of International Human Rights - Muhammad Iqbal Rahmatullah; Tomy Michael (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2024)
The discussion of euthanasia is an interesting topic to explore due to the complex legal implications of both active and passive forms of euthanasia. This research will evaluate the perspectives of criminal law and human rights on the practice of euthanasia in Indonesia, as well as seek solutions to the complex dilemma between the needs of society by considering the rights of individuals and the legal norms prevailing in society. In this discussion, a comparison will be made to the regulation of euthanasia in New Zealand which regulates certain requirements. So that the problem analyzed is how the Comparison of Legal Regulations on the Use of Euthanasia in Indonesia and New Zealand in the Framework of Human Rights. This type of research uses normative legal methods. In addition, this research uses the statutory approach method, conceptual approach, and legal comparison approach. The results showed that Indonesia does not have specific regulations regarding euthanasia so that any action that ends a person's life can be subject to criminal articles. Another case with New Zealand which provides special regulations that make the regulations on this matter clear. In some ways it can be seen that the regulations in these two countries are very different where Indonesia prohibits actions that end a person's life while New Zealand provides exceptions to these actions as long as they are carried out in accordance with the law.